Spatial entanglement from off-diagonal long-range order in a Bose-Einstein condensate - Heaney, L; Anders, J; Kaszlikowski, D; Vedral, V (2007)
We investigate spatial entanglement-particle-number entanglement between regions of space-in an ideal bosonic gas. We quantify the amount of spatial entanglement around the transition temperature for condensation (TC) by probing the gas with two localized two-level systems. We show that spatial entanglement in the gas is directly related to filling of the ground-state energy level and therefore to the off-diagonal long-range order of the system and the onset of condensation. © 2007 The American Physical Society.